2002
DOI: 10.1182/blood-2002-03-0765
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the treatment of acquired factor VIII inhibitors

Abstract: Autoantibodies against factor VIII (FVIII) are rare but can cause life-threatening bleeding requiring costly factor replacement and prolonged immunosuppression. We report 4 consecutively treated patients whose acquired FVIII inhibitors responded rapidly to immunosuppressive regimens that included rituximab, a monoclonal antibody against CD20 ؉ B cells. Three patients had spontaneously occurring inhibitors. The fourth, a patient with mild hemophilia A, developed both an autoantibody and an alloantibody followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
2
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(157 citation statements)
references
References 20 publications
4
142
2
9
Order By: Relevance
“…Rituximab, a chimeric anti-CD20 monoclonal antibody, causes a rapid depletion of B cells [9]. Although rituximab was originally introduced for the treatment of malignant lymphomas [10,11], several recent studies have shown that rituximab may also be effective in the treatment of ITP and other autoimmune diseases [12,19,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The current results of all published case reports and clinical trials using rituximab in the treatment of immune thrombocytopenias have most recently been reported showing an overall response rate of about 50% [34].…”
Section: Introductionmentioning
confidence: 99%
“…Rituximab, a chimeric anti-CD20 monoclonal antibody, causes a rapid depletion of B cells [9]. Although rituximab was originally introduced for the treatment of malignant lymphomas [10,11], several recent studies have shown that rituximab may also be effective in the treatment of ITP and other autoimmune diseases [12,19,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The current results of all published case reports and clinical trials using rituximab in the treatment of immune thrombocytopenias have most recently been reported showing an overall response rate of about 50% [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in young female patients, such treatment can compromise fertility (Maillard et al, 2006). In contrast, rituximab was well tolerated with few side effects and no infectious complications reported in patients with acquired haemophilia (Wiestner et al, 2002;Fischer et al, 2003;Jy et al, 2003;Stasi et al, 2004;Aggarwal et al, 2005;Clatworthy & Jayne, 2006;Maillard et al, 2006;Santoro et al, 2007), and was an effective alternative for patients unable to receive cytotoxic therapy (Jy et al, 2003;Marietta et al, 2003;Stasi et al, 2004;Berezné et al, 2006;Maillard et al, 2006). Aggarwal et al (2005) have proposed an algorithm for the treatment of autoimmune haemophilia.…”
Section: Use Of Rituximab In Acquired Haemophiliamentioning
confidence: 99%
“…56 A metodologia consiste de infusões intravenosas de rituximab (anticorpos monoclonais anti-CD20) que se liga às células B e iniciam um processo de lise celular (via sistema do complemento ou apoptose). 57,58 Esta opção de tratamento tem se mostrado bastante eficiente e uma grande quantidade de estudos relaciona a sua eficácia no tratamento de anticorpos inibidores de FVIII em indivíduos com hemofilia adquirida. [59][60][61][62] Entretanto, notificações de reações adversas relacionadas ao uso do medicamento têm sido emitidas e casos de síndrome de liberação excessiva de citocinas com resultado fatal já foram relatados.…”
Section: Tratamento Das Crises Hemorrágicas Na Presença Do Inibidorunclassified